Atomistic model of diopside–K-jadeite (CaMgSi2O6–KAlSi2O6) solid solution - Vinograd, V.; Safonov, O.; Wilson, D.; Perchuk, L.; Bindi, L.; Gale, Julian; Winkler, B. (Pleiades Publishing Ltd., 2010)
Atomistic model was proposed to describe the thermodynamics of mixing in the diopside–K-jadeite solid solution (CaMgSi2O6–KAlSi2O6). The simulations were based on minimization of the latticeenergies of 800 structures within a 2 × 2 × 4 supercell of C2/c diopside with the compositions betweenCaMgSi2O6 and KAlSi2O6 and with variable degrees of order/disorder in the arrangement of Ca/K cations in M2 site and Mg/Al in Ml site. The energy minimization was performed with the help of a force-field model. The results of the calculations were used to define a generalized Ising model, which included 37 pair interaction parameters. Isotherms of the enthalpy of mixing within the range of 273–2023 K were calculated with a Monte Carlo algorithm, while the Gibbs free energies of mixing were obtained by thermodynamic integration of the enthalpies of mixing. The calculated T–X diagram for the system CaMgSi2O6–KAlSi2O6 at temperatures below 1000 K shows several miscibility gaps, which are separated by intervals of stability of intermediate ordered compounds. At temperatures above 1000 K a homogeneous solid solution is formed. The standard thermodynamic properties of K-adeite (KAlSi2O6) evaluated from quantum mechanical calculations were used to determine location of several mineral reactions with the participation of the diopside–K-jadeite solid solution. The results of the simulations suggest that the low content of KalSi2O6 in natural clinopyroxenes is not related to crystal chemical factors preventing isomorphism, but is determined by relatively high standard enthalpy of this end member.